2018
DOI: 10.1016/j.cose.2018.03.015
|View full text |Cite
|
Sign up to set email alerts
|

Collateral damage of Facebook third-party applications: a comprehensive study

Abstract: Third-party applications on Facebook can collect personal data of the users who install them, but also of their friends. This raises serious privacy issues as these friends are not notified by the applications nor by Facebook and they have not given consent. This paper presents a detailed multi-faceted study on the collateral information collection of the applications on Facebook. To investigate the views of the users, we designed a questionnaire and collected the responses of 114 participants. The results sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 54 publications
0
31
0
Order By: Relevance
“…Research has also suggested that conscientious individuals are reluctant online users and particularly wary about sharing personal information (Ross et al, 2009). Given the responsible nature of conscientious individuals, they are also likely to be concerned about the level of access their friends' Facebook apps have to their personal information and vice versa (Symeonidis et al, 2018). In support of this finding, Codish and Ravid (2014) found that individuals high in conscientiousness dislike mechanisms that raise awareness of performance-related information (e.g., leader boards).…”
Section: H1bmentioning
confidence: 99%
See 2 more Smart Citations
“…Research has also suggested that conscientious individuals are reluctant online users and particularly wary about sharing personal information (Ross et al, 2009). Given the responsible nature of conscientious individuals, they are also likely to be concerned about the level of access their friends' Facebook apps have to their personal information and vice versa (Symeonidis et al, 2018). In support of this finding, Codish and Ravid (2014) found that individuals high in conscientiousness dislike mechanisms that raise awareness of performance-related information (e.g., leader boards).…”
Section: H1bmentioning
confidence: 99%
“…Members of social groups take it upon themselves to regulate their own behavior in line with the extant social norms of the larger group. There are, however, occurrences in which the use of Facebook apps affects other users, specifically those in a person's list of friends ( Symeonidis et al., 2018 ). These apps harvest personal information from friends and thus also increases an individual's vulnerability to privacy violations.…”
Section: Research Model and Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…In a follow-up work, Symeonidis et al revisit their initial investigation in the light of the Cambridge Analytica scandal and complement it with a legal analysis based on the General Data Protection Regulation of the European Union (EU GDPR) [Symeonidis et al 2018].…”
Section: Multimedia Datamentioning
confidence: 99%
“…All these data have enormous potential for data mining methods and subsequent analysis. We already have sufficient capabilities (hardware and software) to process, store, organize, and evaluate them, but unfortunately, this is not accessible to third parties [32,33,34].…”
Section: A Customer Data Collectionmentioning
confidence: 99%